2023
DOI: 10.1007/s10608-023-10379-4
|View full text |Cite
|
Sign up to set email alerts
|

YES, WE COPE: Dyadic Coping as a Mediator Between Perceived Relationship Quality and Emotional Representation of COVID-19

Abstract: Background The COVID-19 pandemic has brought about social changes that have impacted the functioning and dynamics of couples in a romantic relationship, arising from the overwhelming amount of added stress they have endured. Specifically, the divorce rate in Portugal has increased after lockdown, which underscores the adverse consequences of COVID-19 on couples. A lower quality of the couple’s relationship may worsen the emotional representation of COVID-19; however, the literature suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…An explanation for the heightened risk among couples already contemplating separation prior to COVID-19 lies in the stress overflow phenomenon that we described before, which made the relationship more susceptible. Empirical evidence robustly indicates that couples experiencing frequent coronavirus-related conflict or those unable or unwilling to engage in mutual coping were more likely to report lower satisfaction, decreased in sexual and intimate encounters and conflicts (Donato et al, 2021;From et al, 2023;Luetke et al, 2020;Relvas et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An explanation for the heightened risk among couples already contemplating separation prior to COVID-19 lies in the stress overflow phenomenon that we described before, which made the relationship more susceptible. Empirical evidence robustly indicates that couples experiencing frequent coronavirus-related conflict or those unable or unwilling to engage in mutual coping were more likely to report lower satisfaction, decreased in sexual and intimate encounters and conflicts (Donato et al, 2021;From et al, 2023;Luetke et al, 2020;Relvas et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, these variables also underwent scrutiny in the context of the COVID-19 pandemic. Most of the research indicated that the pandemic-induced stress, anxiety, and uncertainty generally adversely affected relationship quality (Balzarini, et al, 2023;Pietromonaco, & Overall, 2021;Relvas et al, 2023), dyadic adjustment, and adaptive coping mechanisms (Donato et al, 2021;Romeo, et al, 2022). It is worth noting that these studies predominantly offered cross-sectional insights, while a singular longitudinal study revealed there were no changes in couple satisfaction over a one-year follow-up period (Galdiolo, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Apesar do enriquecimento família-trabalho já ser explorado (e.g., Bodenmann et al,2011;Jiaqing, 2014;Relvas et al, 2023), existe a lacuna na literatura acerca de quais são os impactos específicos dos recursos e estratégias de regulação provenientes da família para cada fator do modelo JD-R.…”
Section: Justificativaunclassified
“…Estudos que investigam o impacto negativo dessa interface mostram que pessoas com maiores percepções de conflito família-trabalho apresentam também maiores níveis de estresse e menores níveis de engajamento no trabalho (e.g., Ribeiro et al, 2023). Por outro lado, há também pesquisadores que se debruçam a investigar os impactos positivos da relação família-trabalho, mostrando que equilíbrio entre essas duas áreas é benéfico para o indivíduo, tanto na vida profissional como pessoal (e.g., Bodenmann et al, 2016;Gabardo-Martins et al, 2016;Jiaqing, 2014;Relvas et al, 2023;Timms et al, 2015).…”
Section: Introductionunclassified
See 1 more Smart Citation